PHYTOCHEMICAL EXPLORATION OF TURMERIC AND ETHNOPHARMACY IN BENGKALA VILLAGE FOR DIABETES PREVENTION AS A SUPPLEMENT TO PHARMACOGNOSY TEACHING AT VOCATIONAL SECONDARY SCHOOLS - Putri Layani Gea; I Nyoman Tika; Siti Maryam (Adisam Publisher, 2026)
The teaching of pharmacognosy at vocational schools specialising in pharmacy generally still focuses on theoretical concepts and does not yet sufficiently link the subject matter to the practical use of medicinal plants in the students’ local communities. This study aims to describe the ethnopharmaceutical practices involved in the processing of turmeric (Curcuma longa L.) in Bengkala Village, to examine the phytochemical composition of turmeric based on a literature review, and to integrate these findings as a supplement to pharmacognosy teaching based on local knowledge. The study employed a descriptive qualitative approach, utilising data collection techniques such as observation, interviews, documentation, a literature review, and a descriptive organoleptic test of the turmeric drink. The results indicate that the community in Bengkala Village processes turmeric into a traditional herbal drink through the steps of washing, grinding, boiling and straining. The results of the organoleptic test showed that turmeric ‘loloh’ has a brownish-yellow colour, a characteristic turmeric aroma, a moderately bitter taste, and a relatively thin texture. A literature review indicated that turmeric rhizomes contain secondary metabolites such as curcuminoids, flavonoids, essential oils and tannins, which have the potential to exhibit antioxidant and anti-inflammatory activity, as well as supporting the regulation of blood glucose levels. These ethnopharmaceutical findings and phytochemical studies were subsequently incorporated into pharmacognosy teaching materials, covering the identification of rhizome crude drugs, simple water-based extraction methods, and an introduction to the secondary metabolites of medicinal plants. This integration has resulted in contextual and relevant supplementary learning materials to support the teaching of pharmacognosy at vocational schools specialising in pharmacy.